Landscape ecological risk assessment study of the Yunnan section of the Tropic of Cancer - Hui, Ye; Die, Bai; Jinliang, Wang; Shucheng, Tan; Shiyin, Liu; Xiaoping, Wu (Ecological indicators, 2024)
•Natural landscapes are vital for regional ecosystem stability and function.•Human engineering activities have a great impact on the natural landscape.•Woodland and cropland have the least impact on ecological risk levels.•Farming, urbanization, deforestation, population growth worsen ecological risks. Natural landscapes constitute a vital component of ecosystems, and their stability and diversity are essential in maintaining regional ecosystem functions. The scientific and rational assessment of ecological risks in regional landscapes is crucial for activities such as ecosystem security evaluation, optimization of ecosystem function zoning, and establishment of landscape security patterns. We focused on the Yunnan section of the Tropic of Cancer, employing Landsat 8 remote sensing data to categorize landscape types and construct ecological risk indices. Using software platforms such as ArcGIS, GEE, and Fragstats4.2, an evaluation and spatial characteristics analysis of the ecological risk in the Yunnan section of the Tropic of Cancer was conducted, yielding the following findings: ① The overall level of ecological risk within the Yunnan section of the Tropic of Cancer is relatively low. The lower ecological risk zone covers an area of 19,100.35 km2, accounting for 34.09 % of the total study area, while the higher ecological risk zone spans 2,032.91 km2, constituting only 3.63 % of the total study area. ② Landscape types in areas of lower and low ecological risk are predominantly characterized by woodland landscapes, comprising 90.93 % and 62.19 %, respectively. Conversely, areas with high ecological risk and higher ecological risk are dominated by cultivated land, representing 67.75 % and 95.61 %, respectively. This underscores the importance of strengthening forestry development and controlling the expansion of cultivated land to mitigate regional landscape ecological risks. ③Regions with higher ecological risks in the landscape are primarily in the northwestern part of Yanshan County, the southern part of Gengma County, and the northern part of Wenshan city. These areas are susceptible to the impacts of intense farming, extreme weather, and the karst geological environment. In contrast, regions with high ecological risks are in the central and eastern parts of Mojiang County, the western part of Yanshan County, and the northern part of Wenshan city. These areas are mostly influenced by urban economic development, extensive construction projects leading to deforestation and grassland degradation, and the substantial demand for arable land due to a significant population increase. ④ The spatial pattern of ecological risk in the Yunnan section of the Tropic of Cancer, as indicated by Moran's I index, is positive and exceeds 0.6. The Z score significantly surpasses the reference value of 2.58, with p < 0.01. This indicates a strong degree of spatial autocorrelation and a high positive correlation in the spatial distribution characteristics.